C-Kit inhibitors for unresectable or metastatic mucosal, acral or chronically sun-damaged melanoma: a systematic review and one-arm meta-analysis. (November 2021) - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Kohl, Christoph; Erdmann, Michael; Berking, Carola; Heppt, Markus V.
Abstract: Background: Activating genomic alterations of the receptor tyrosine kinase KIT are found preferentially in certain melanoma subtypes such as acral and mucosal melanoma or melanoma arising in chronically sun-damaged skin. However, the therapeutic value of c-Kit inhibitors for these subtypes currently remains unclear. Objectives: The objective of this study was to summarise the efficacy and safety of c-Kit inhibitors for unresectable or metastatic mucosal, acral or chronically sun-damaged melanoma. Methods: We performed a systematic literature research in MEDLINE, Embase and CENTRAL and hand searched pertinent trial registers and conference abstracts for eligible trials until 23rd June 2020. Results were pooled using a random-effects model to calculate pooled proportions of objective response rates (ORRs) and severe adverse events (sAEs) from unselected KIT mutant or amplified cohorts. Results: Nineteen single-arm studies with an overall sample size of 601 patients were included. The studies investigated imatinib (n = 8), nilotinib (n = 7), dasatinib (n = 3) and sunitinib (n = 1). The pooled ORR for all inhibitors was 15% (95% confidence interval [CI]: 12–18%). Subgroup analysis revealed the highest ORR (20%; 95% CI: 14–26%) for nilotinib. The ORR for mucosal melanoma was 14% (95% CI: 6–24%) and 22% for acral lentiginous melanoma (95% CI: 14–30%). At least one sAE was reported in 42% of patients (95% CI: 34–50%). Conclusions: c-Kit inhibitors represent a valuable treatment option for patients with KIT-mutant melanoma, in particular for mutations of exons 11 and 13. Furthermore, high-quality trials are urgently needed to investigate putative combinations of specific targeted therapies with immunotherapy. Highlights: The therapeutic value of c-Kit inhibitors in rare melanoma subtypes is unclear. Twenty-one studies with n = 649 patients were identified in a systematic literature research. Pooled objective response rate was 15% (95% confidence interval: 11–20%) for all c-Kit inhibitors. Combination of c-Kit inhibitors with immunotherapy should be further investigated.